2021
DOI: 10.20882/adicciones.1561
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias de género en percepciones sobre violencia sexual, igualdad y agresiones sexuales facilitadas por drogas en ocio nocturno

Abstract: Diferencias de género en percepciones sobre violencia sexual, igualdad y agresiones sexuales facilitadas por drogas en ocio nocturno Gender-based differences in perceptions about sexual violence, equality and drug-facilitated sexual assaults in nightlife contexts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(47 reference statements)
0
2
1
Order By: Relevance
“…Future studies should also examine the role of these variables in the comprehension of male students. Results could differ from ours, given that it has been suggested that prior knowledge and emotions that men experience when reading about GBV differ from those of women [99]. Another limitation of this study is that we did not examine the role of emotional intelligence.…”
Section: Commentcontrasting
confidence: 82%
“…Future studies should also examine the role of these variables in the comprehension of male students. Results could differ from ours, given that it has been suggested that prior knowledge and emotions that men experience when reading about GBV differ from those of women [99]. Another limitation of this study is that we did not examine the role of emotional intelligence.…”
Section: Commentcontrasting
confidence: 82%
“…There is a normalized perception in which the contexts of night life and drinking alcohol facilitate SV [ 36 ]. In the case of women, they express this from a position of imagining that situation as victims of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the relationship between these adolescent beliefs and the stage immediately after, moving in from adolescence to young adulthood, is ascertained . Findings from a recent study with a large university sample report that a large section of young Spaniards does not perceive certain types of violence against women showing, for example, that in nightlife contexts, the consumption of drugs and alcohol is used to justify it, an idea again shared especially by the group of boys (Prego-Meleiro et al ., 2021) . This data is consistent with another from a Spanish government source (DGVG, 2018) stating that the cause of rape is alcohol for nearly 50% of the men surveyed and 45% of the women .…”
Section: Introductionmentioning
confidence: 99%